Using ICT to support reflection in pre-service mathematics teacher education - Ponte, João Pedro da (2011)
This paper analyses a virtual supervision setting (e-mail and forum) during the practicum in a pre-service secondary school mathematics teacher education program. It is a study of the authors’ own professional practice using a qualitative-interpretative approach and case studies of student teachers. The results show that the setting was significant for pre-service teachers who had a more reflective attitude, but was seen as a burden by the others. The forum enabled fruitful reflections and discussions and e-mail was mostly used for organizational matters. In the future, attention must be paid to the role of the educational supervisor in fostering participation in the forum and use of e-mail.